2010
DOI: 10.1029/2009jd011957
|View full text |Cite
|
Sign up to set email alerts
|

Two types of precipitation particle distribution in convective cells accompanying a Baiu frontal rainband around Okinawa Island, Japan

Abstract: [1] Polarimetric radar variables and ground-based raindrop size distributions (DSDs) of two convective cells in a Baiu frontal rainband over the Okinawa region were analyzed to clarify the precipitation particle distributions in convective cells with low echo top heights. One cell existed in the stratiform rain zone, and the other was in the convective rain zone of the rainband. Both cells had echo top (30 dBZ) heights of approximately 5.5 km above sea level, with large radar reflectivity (Z h ) greater than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…9a). The foregoing features of vertical profiles of polarimetric radar variables have also been reported in embedded convective rainfalls in Baiu front events during the rainy season in East Asia (Shusse et al 2009;Oue et al 2010).…”
Section: A Hydrometeors At Around the 08c Level In The CML Regionmentioning
confidence: 81%
“…9a). The foregoing features of vertical profiles of polarimetric radar variables have also been reported in embedded convective rainfalls in Baiu front events during the rainy season in East Asia (Shusse et al 2009;Oue et al 2010).…”
Section: A Hydrometeors At Around the 08c Level In The CML Regionmentioning
confidence: 81%
“…Comparisons with Oue et al . [, ] suggest that the stratiform precipitation in this study had DSDs with higher number concentrations of smaller raindrops than observed previously in convective cells in a Baiu frontal convective precipitation region around Okinawa Island. The DSDs also suggest the presence of larger raindrops than observed previously in convective cells embedded in a Baiu frontal stratiform precipitation region around Okinawa Island.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the raindrop size distribution (DSD) around Okinawa Island have been the focus of several studies [ Bringi et al ., ; Shusse et al ., ; Oue et al ., , ]. Shusse et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Meiyu-Baiu front brings heavy rainfall in east China, mainly in the Yangtze-Huaihe River basin, and over the southern part of Japan. In recent years, authors have studied the characteristics of DSDs during the Baiu period in Japan (e.g., Harimaya 2003, 2005;Shusse et al 2009;Oue et al 2010); however, not much is known about the DSDs in the Meiyu season in China, mainly because of the lack of DSD measurements.…”
Section: Introductionmentioning
confidence: 99%